Comparison of the Outcome of Fistulectomy Versus Fistulotomy in Treatment of Fistula in Ano - Sadia Mannan, Ali Akbar, Rashid Mehmood, Wajahat Amir, Humayun Siiddique, Manzar Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the outcome of fistulectomy versus fistulotomy in treatment of fistula in ano. Study design: Randomized Controlled Trial Setting and duration: Department of General Surgery, CMH, Lahore from March 2019 to september2019. Methodology: Through the outpatient department of the general surgery unit at the Combined Military Hospital in Lahore, a total of 112 patients who met the selection criteria were invited to participate in the study. After that, each of the patients was assigned a number and placed into one of two groups. In the group A patients, a fistulectomy was performed. Fistulotomy was performed on members of group B. Each and every operation was performed under spinal anaesthetic. The number of minutes required for the operation was tallied beginning with the incision and continuing through the wound dressing. After surgery, patients were moved to the surgical ward to recover and get follow-up care for a period of twenty-four hours. After that, patients were monitored for a total of four weeks after their operations. It was determined how many days the wound would take to heal in total. SPSS was utilized in order to perform the data analysis. Results: In the fistulectomy group, the mean surgical time was 33.00 minutes with a standard deviation of 4.31 minutes, whereas in the fistulotomy group, the mean operative time was 19.55 minutes with a standard deviation of 2.87 minutes. In the fistulectomy group, the average length of time needed for healing was 31.84 4.67 days, whereas in the fistulotomy group, the average length of time needed for healing was 20.63 4.95 days. Conclusion: Fistulotomy is a therapeutic option that is both straightforward and successful for treating simple perianal fistulas. Keywords: Fistulectomy, fistulotomy, fistula in ano, operative time, duration of healing